Knowledge Brokering and Organizational Innovation: Founder Imprinting Effects - Hsu, David H.; Lim, Kwanghui (Organization Science, 2014)
We empirically examine the innovation consequences of organizational knowledge brokering, the ability to effectively apply knowledge from one technical domain to innovate in another. We investigate how organizational innovation outcomes vary by founders’ initial mode of venture ideation. We then compare how firms established with knowledge-brokering-based ideation differ in their methods of sustaining ongoing knowledge-brokering capacity compared with firms not established in such a manner. We do so by tracking all the start-up biotechnology firms founded to commercialize the then-emergent recombinant DNA technology (the sample of initial knowledge brokers) together with a contemporaneously founded sample of biotechnology firms that did not license the DNA technology (the sample of initial nonbrokers). Our results suggest that (a) ongoing knowledge brokering has an inverted U-shaped relationship with innovative performance in general; (b) initial knowledge brokers have a positive imprinting effect on their organizations’ search patterns over time, resulting in superior performance relative to nonbrokers; and (c) initial nonbrokers rely more on external channels of sourcing knowledge, such as hiring technical staff, relative to initial brokers, reinforcing the imprinting interpretation. The described imprinting mechanism differs from extant mechanisms such as partner affiliation- and trigger-based mechanisms in explaining entrepreneurial performance differentials.